From science to adapted patient education in retinal optical coherence tomography: How terminology influences diagnostic understanding - Galli, Fabio (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2022)
Optical Coherence Tomography (OCT) in retinal imaging has evolved rapidly over the last twenty years. Along with these changes in technology, the nomenclature and relationships between healthcare professionals and patients have changed as well. How to translate the complex language of the field such that patients can understand it better is the focus of this paper.